Labor in the Boardroom - Simon Jäger; Benjamin Schoefer; Jörg Heining (Center for Economic Studies and ifo Institute (CESifo), 2019)
We estimate the effects of a mandate allocating a third of corporate board seats to workers (shared governance). We study a reform in Germany that abruptly abolished this mandate for certain firms incorporated after August 1994 but locked it in for the older cohorts. In sharp contrast to the canonical hold-up hypothesis – that increasing labor's power reduces owners' capital investment –we find that granting formal control rights to workers raises capital formation. The capital stock, the capital-labor ratio, and the capital share all increase. Shared governance does not raise wage premia or rent sharing. It lowers outsourcing, while moderately shifting employment to skilled labor. Shared governance has no clear effect on profitability, leverage, or costs of debt. Overall, the evidence is consistent with richer models of industrial relations whereby shared governance raises capital by permitting workers to bargain over investment or by institutionalizing communication and repeated interactions between labor and capital.
Keywords: G00; J00; J53; J54; 330; industrial relations; corporate governance; codetermination; investment